Pengembangan Media Pembelajaran Permainan Monopoli Edukatif Berbasis Website Materi Kebugaran Jasmani pada Siswa Fase D Kelas VIII SMP - Shefyra Putri Islami; Siti Nurrochmah (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
The advancement of science and technology and 21st century education requiresinnovative learning media that integrates digital technology and games. However, the use of digital game-based learning media in physical education is still limited. This study was conducted with the aim of assessing the feasibility of a web-based monopoly game learning media that contains physical fitness material for eighth grade students at SMP Negeri 20 Malang. The method used was R&D or research and development through the adaptation of the ADDIE development model. The process involved physical fitness experts, learning experts, media experts, field practitioners (PJOK teachers), and students as a test group. The development stages included needs analysis, game concept development, prototype creation, expert assessment, and small and large group trials. The assessment results showed a very high level of feasibility: 97% based on physical fitness experts, 93% based on learning experts, 93% based on media experts, and 99% based on practitioner assessments. Meanwhile, the small group trial resulted in a score of 91%, and the large group trial resulted in a mean score of 93%, which is also considered very feasible. The resulting learning media is considered feasible for use as a supporting medium for physical education, especially physical fitness. The novelty of this research lies in the website-based monopoly game learning media for physical fitness material, which is in line with the development of digital technology in the field of education.